A glucose-depleting silica nanosystem for increasing reactive oxygen species and scavenging glutathione in cancer therapy. Issue 89 (21st October 2019) - Ong, Wee Kong; Jana, Deblin; Zhao, Yanli
Abstract : A novel silica nanosystem is fabricated to convert intracellular glucose to hydrogen peroxide for enhancing reactive oxygen species level and triggering p -quinomethane release to scavenge glutathione, achieving synergistic anticancer treatment. Abstract : Cancer cells adapt to cellular oxidative stress by increasing glutathione (GSH). An organically modified silica nanosystem (ORMOSIL@GOx) was fabricated to achieve a lethal level of oxidative stress in cancer cells by depleting intracellular GSH while increasing reactive oxygen species.